Investigation of different leaf characters on Muskmelon cultivars possessing grades of resistance to downy mildew disease - M. MAHAJAN,; M. DHILLON,; K BHARDWAJ, (International Journal of Pharma and Bio Sciences, 2017)
Downy mildew caused by Pseudoperonodporacubensis (Berk. and Curt.) Rostow is one of the most destructive fungal diseases of muskmelon (Cucumismelo L.) posing a serious problem in the successful cultivation of this crop. The pathogen penetrates the leaf through stomata. With this in view leaf anatomy of 42 muskmelon genotypes (19 resistant and 23 susceptible) was examined in relation to their resistance/susceptibility to the disease. Their disease score was rated using a 0-5 scale. The results showed that stomatal size, frequency and index were significantly higher in susceptible genotypes, whereas, the resistant genotypes had higher frequencies of large trichomes. Thickness of cuticle, thickness of palisade tissue, palisade proportion and palisade index values were significantly higher in resistant genotypes indicating compact arrangement of the palisade cells thus preventing further spread of the pathogen. The results indicated that leaf epidermal and other anatomical characteristics may act as structural barriers against penetration by downy mildew pathogen. Evaluation for these characteristics may prove useful for early and preliminary screening of newly evolved muskmelon genotypes when assessing their resistance/susceptibility to downy mildew infection in large breeding populations.